Techno Economic Evaluation and Feasibility Analysis of a Hybrid Net Zero Energy Building in Pakistan: A Case Study of Hospital - Arif, Saba; Taweekun, Juntakan; Ali, Hafiz Muhammad; Theppaya, Thanansak (Frontiers in Energy Research, 2021)
The current study is an economic evaluation and feasibility study of hybrid micro grid Net Zero Energy Buildings in Pakistan. Hence, Net Zero Energy approach is proposed for a two story hospital building situated at Taxila, Pakistan. Consequently, for the designing of hybrid Net Zero Energy Building, solar radiation potential of the subject location and electricity usage of the hospital is estimated. The proposed hybrid micro grid Net Zero Energy Building comprises of photovoltaic modules and converters. However, thermal load is computed as a grid connected hybrid system. Economic evaluation is performed by using economic indicators of the net present cost and the payback period. Also, initial and operational costs are determined, to check the profitability of the project. Results show that, analysis is cost effective and has a payback period of 2.53y. Additionally, per unit cost of electricity reduces to 0.12USD/kWh. Moreover, energy produced by a hybrid system is 10.24% more economical than the pre working grid system. Results explain reduction in cost of energy, profit margin in electricity generation, increase in electricity production and feasibility of hybrid Net Zero Energy Buildings in Pakistan. Research will help to develop an approach toward IEA task 47 in Pakistan with addition to development of simulation based installations of Net Zero Energy Buildings in the health sector in Pakistan.